Existence of Pseudo Almost Automorphic Solutions for the Heat Equation with -Pseudo Almost Automorphic Coefficients - Agarwal RaviP; Diagana Toka (Boundary Value Problems, 2009)
We obtain the existence of pseudo almost automorphic solutions to the -dimensional heat equation with -pseudo almost automorphic coefficients.